2022
DOI: 10.1088/1748-0221/17/01/c01035
|View full text |Cite
|
Sign up to set email alerts
|

Impact of X-ray induced radiation damage on FD-MAPS of the ARCADIA project

Abstract: Recent advancements in Monolithic Active Pixel Sensors (MAPS) demonstrated the ability to operate in high radiation environments of up to multiple kGy’s, which increased their appeal as sensors for high-energy physics detectors. The most recent example in such application is the new ALICE inner tracking system, entirely instrumented with CMOS MAPS, that covers an area of about 10 m2. However, the full potential of such devices has not yet been fully exploited, especially in respect of the size of the active ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, the simulations show overall lower capacitances, which could originate from an underestimated concentration of positive oxide charges N ox in the SiO 2 layer. As described in previous works, we found that the single-pixel capacitance is impacted by an electron accumulation layer below the Si-SiO 2 interface [3,11]. The simulations include an oxide charge concentration of 6.5 × 10 10 cm −3 , based on the Hamamatsu parametrisation of the new Perugia model [7].…”
Section: Characterisation Of Passive Pixel Matrices and Tcad Simulati...mentioning
confidence: 65%
“…However, the simulations show overall lower capacitances, which could originate from an underestimated concentration of positive oxide charges N ox in the SiO 2 layer. As described in previous works, we found that the single-pixel capacitance is impacted by an electron accumulation layer below the Si-SiO 2 interface [3,11]. The simulations include an oxide charge concentration of 6.5 × 10 10 cm −3 , based on the Hamamatsu parametrisation of the new Perugia model [7].…”
Section: Characterisation Of Passive Pixel Matrices and Tcad Simulati...mentioning
confidence: 65%
“…CV measurements were performed as well to estimate the pixel capacitance and compare them with simulation results. The preliminary results of the electrical characterization of the passive pixel arrays are reported in [15]. Table 1 contains the measured full depletion and punch-through voltages and the pixel capacitance in full depletion condition extracted from TCAD simulations for an applied nwell voltage of 0.8 V.…”
Section: Laser Characterizationmentioning
confidence: 99%
“…In order to investigate the effect of the applied reverse bias voltage (V bias ) on the signal evolution, we performed measurements on the pixel matrices varying V bias in a voltage range that starts below V depl and ends above V PT . The punch through voltage does not represent an absolute limit to the applicable bias voltage since the punch through current is still in the nA range with a V bias exceeding V PT by several volts [15]. For this reason, we can apply a voltage higher than V PT while still granting a low power consumption for the detector.…”
Section: Pixel Dynamic Responsementioning
confidence: 99%